2016
DOI: 10.1111/jmi.12415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of morphological representative sample sizes for nanolayered polymer blends

Abstract: The size of representative microstructural samples obtained from atomic force microscopy is addressed in this paper. The case of an archetypal one-dimensional nanolayered polymer blend is considered. Image analysis is performed on micrographs obtained through atomic force microscopy, yielding statistical data concerning morphological properties of the material. The variability in terms of microstructural morphology is due to the thermomechanical processing route. The statistical data is used in order to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 26 publications
(34 reference statements)
5
24
0
1
Order By: Relevance
“…The average experimental thicknesses of PE−PEgMA layers x PE−PEgMA and their standard deviation std PE−PEgMA were calculated from the measurement of at least 10% of the total number of layers. 29 They are reported in Table 1 and are in reasonable agreement with their respective theoretical thickness x thPE−PEgMA . std PE−PEgMA appears slightly higher than for other multilayer systems, 29 which may be due to the relatively high viscosity ratios between polymers (Table S1, Supporting Information).…”
supporting
confidence: 78%
“…The average experimental thicknesses of PE−PEgMA layers x PE−PEgMA and their standard deviation std PE−PEgMA were calculated from the measurement of at least 10% of the total number of layers. 29 They are reported in Table 1 and are in reasonable agreement with their respective theoretical thickness x thPE−PEgMA . std PE−PEgMA appears slightly higher than for other multilayer systems, 29 which may be due to the relatively high viscosity ratios between polymers (Table S1, Supporting Information).…”
supporting
confidence: 78%
“…This small deviation between mean experimental and theoretical layer thickness may either be due to slight changes in the extruders throughput during extrusion (which will modify the film composition) and/or to the sampling size (i.e. the number of layers measured in the sample compared to the total number of layers) used to determine the mean, as discussed in a previous study [60]. Still, there is a satisfactory agreement between the (targeted) MAM theoretical layer thickness and the mean experimental one for all the samples studied.…”
Section: Resultsmentioning
confidence: 95%
“…a few pixels in terms of AFM imaging, it is critical to analyze all possible sources of error. These sources of error were studied extensively in a previous article, 56 Based on statistical parameters (K a constant and γ the scaling-law exponent) determined from a…”
Section: Image Analysismentioning
confidence: 99%
“…representative-volume-element study for PS layers, 56 and knowing the nominal value h nom , the number of performed AFM images, and the size of the images, it was possible to determine the relative uncertainty rel of the thickness measurement due to sampling for each film. Calculations have shown that the sampling uncertainty varied between 5% and 30%.…”
Section: Image Analysismentioning
confidence: 99%